Decolonising continuing teacher professional development in the teaching of physical science through improvisation in rural areas - Mabasa, T.; Singh, S. (South African Journal of Higher Education, 2020)
Calls for the decolonisation of higher education in the world and South Africa in particular, has gained momentum since the student protests in 2015 and 2016. This takes place after some efforts have been made to transform and democratise the higher education landscape. Efforts made include: National Commission on Higher Education, White Paper 3 1997, The Higher Education Act of 1997 and the South African Qualifications Authority (SAQA) Act of 1995 which led to the creation of National Qualification Framework (NQF). The policies had promises on issues of access, equity, equality, inclusivity and social justice. After 20 years of democracy, students started to question the progress or lack thereof in the transformation of higher education in South Africa. They started to make demands for access, free education, decolonisation of the curriculum, changes in the pedagogy and epistemic practices. They also demanded the removal of certain statues on some of the campuses. The protests jolted some academics to start debating and writing about the decolonisation of higher education in South Africa. This was done by picking up different aspects that were made points of focus in terms of decolonisation. Consequently, some academics focused on the decolonisation of the curriculum, some on the higher education system whilst others focussed on teacher education. In this article, we intend to contribute to the debate by focusing on Continuing Teacher Professional Development (CTPD) that is an aspect within teacher education. The focus on CTPD was prompted by the fact that not much has been done on the decolonisation of CTPD in South Africa. Furthermore, this is a critical area, because unless teachers are empowered and reskilled to drive the decolonisation process, they may resist and ultimately render the whole process unworkable. It is based on the study that was conducted, focusing on CTPD in the teaching of physical sciences in some of the rural schools in Limpopo Province. The choice of physical sciences was because physical sciences is a gateway subject and most physics sciences teachers in Limpopo Province are based in rural areas. Generally, these schools do not have the appropriate facilities and equipment to teach physical science. Physical sciences teachers also face many challenges such as negative perception about the subject, lack of resources, limited room for professional development, poor teacher training, and inadequate support from within the school and the Provincial Department of Education. This study focussed on creativity and teacher empowerment by enabling physical sciences teachers to reflect on their implementation of science inquiry. Physical sciences teachers were empowered to be creative in handling scientific inquiry especially in the absence of the necessary scientific equipment. The study was conduct at a Higher Education Institution (HEI) in Limpopo Province where teachers, from rural schools, are specifically invited to the university for the National Science Week, which included a component of ongoing Continuing Teacher Profession Development (CPTD). During the National Science Week physical sciences teachers attend an in-service workshop on Improvisation in Science. Ninety (90) physical sciences teachers participated in this study. Data were generated by using a questionnaire and unstructured interviews. The findings of the study revealed that the success of CTPD is not so much in spending more funds in CTPD programmes, but it is in the approach that is used to prepare teachers to respond appropriately to the needs and the demands of the classroom environment. The article argues that the decolonisation process should prioritise the CTPD programmes at universities. This is due to the fact that teachers as agents of change need to be empowered and reskilled, so that they can be in the forefront of the decolonisation process. This can be achieved by adopting a transformative approach that encourages improvisation in science teaching. This approach to CPTD demands that teachers’ professional development should shift from the traditional approach to an approach that empowers teachers to be able to make a meaningful contribution to the classes that they teach.